Endometritis puerperal y su relación con el manejo del trabajo de parto, en el instituto materno perinatal de Lima periodo Enero - Diciembre 1994 - Mendoza Cueva, Linda Aurora (1994)
This descriptive study with prospective data collection was conducted in the Obstetric Center of Maternal Perinatal Institute (IMAPE), former Maternity Hospital of Lima, during the period January to December 1994. In the year mentioned utopian 12409 births of which 222 had postpartum postpartum endometritis, constituting 1. 2%, Most of these patients had presented aged 13 - 20 years, constituting 46.4%: whose occupation these, 88.7 home law marriage, at 62.2%; degree of incomplete secondary education. 40.5%; a high rate of primiparous them in 71 23 was observed during labor were performed pelvic exams 7-10 in 66.2%, the duration of labor was 12 hours by 7.3%; There was a low rate of premature rupture of membrane with 20.7%; predominating in the time of 6-12 hours RPM by 71 .7%: in color of amniotic fluid, it was observed that the light color prevailed in 65.43. The vast majority of births were attended by internal Obstetrics in a 47. 2%: with a high prevalence of birth of Schultze type in 68.93 with incomplete membranes in 68.43; with a low rate of abortions of 21.63, and most of them had only a history of abortion in 60.43. Among the most characteristic signs without shots of postpartum endometritis, sorted in descending order are: sub uterine involution in 100% of patients, heat rising 91.4%, pain in the lower abdomen at 78.83, foul smelling lochia in 76.1%.